PERAN MODAL SOSIAL SEBAGAI UPAYA PENGEMBANGAN UMKM DI DESA BATU MERAH KOTA AMBON - Jani Effendy (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2018)
This study aims to look at the role of social capital as an effort to develop UMKM in Batu Merah Village, Ambon City. Home industry is an attractive business sector to note, not only is its development and distribution so rapid but also the dynamics that occur in the industry. This study uses a qualitative approach with descriptive analysis. The selection of informants in this study was carried out by purposive sampling technique, which is the retrieval of data from informants who have been criticized beforehand. The criteria are Micro, Small and Medium Enterprises UMKM in the area. Data collection techniques used are observation, interviews, documentation. The results of this study state that social norms have several functions, among others, as a tool to minimize the possibility of behavioral irregularities in trade, to regulate trade transactions, to help traders get trust from other parties, maintain togetherness and maintain good relations between individuals.